The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/ieam.4433
|View full text |Cite
|
Sign up to set email alerts
|

Open Science in regulatory environmental risk assessment

Abstract: A possible way to alleviate the public skepticism toward regulatory science is to increase transparency by making all data and value judgments used in regulatory decision making accessible for public interpretation, ideally early on in the process, and following the concepts of Open Science. This paper discusses the opportunities and challenges in strengthening Open Science initiatives in regulatory environmental risk assessment (ERA). In this discussion paper, we argue that the benefits associated with Open S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 90 publications
0
6
0
Order By: Relevance
“…Michaels (2008) argues that regulated industries misuse protections for confidential business information (CBI) to protect data on the hazards of their products from public scrutiny (249)(250)(251) and that open data requirements should be applied equally to independent, government-sponsored, and industry-sponsored study data (253-255). 7 Brock et al (2021) is likely to be highly burdensome for scientists, especially those who work with sensitive data such as patient medical records. In this scenario, many researchers would be likely to do open science poorly or simply ignore open science requirements (the findings of Obels et al (2020) suggest this has happened in psychology).…”
Section: Discussionmentioning
confidence: 99%
“…Michaels (2008) argues that regulated industries misuse protections for confidential business information (CBI) to protect data on the hazards of their products from public scrutiny (249)(250)(251) and that open data requirements should be applied equally to independent, government-sponsored, and industry-sponsored study data (253-255). 7 Brock et al (2021) is likely to be highly burdensome for scientists, especially those who work with sensitive data such as patient medical records. In this scenario, many researchers would be likely to do open science poorly or simply ignore open science requirements (the findings of Obels et al (2020) suggest this has happened in psychology).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, to ensure the successful adoption of a paradigm shift in environmental legislation, it is essential to adopt principles of Open Science, making data and judgment criteria transparent and accessible to the public. This transparency is crucial in fostering public trust and acceptance, ultimately facilitating the implementation of effective remediation strategies [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Minelli et al (2021) concluded from their study on open access to research projects and data that, despite the initial and still existing mistrust, it is more than just a best practice because it improves the transparency of research (thus increasing the credibility of researchers, the reproducibility of science and the re-use of products), supports many international initiatives and regulations, and encourages collaboration between scientists from different fields and laboratories. However, the (re)use of these data in a regulatory context needs to be carefully evaluated for relevance and reliability, ideally by using the same criteria for the different studies producing them (Brock et al, 2021).…”
Section: International Cooperation Monitoring Synergies and Data Mana...mentioning
confidence: 99%